FROM THE HUMAN-ENVIRONMENT THEME TOWARDS SUSTAINABILITY – DANISH GEOGRAPHY AND EDUCATION FOR SUSTAINABLE DEVELOPMENT - Thomas SKOU GRINDSTED (European Journal of Geography)
Research on geography in relation to education for sustainable development (ESD), has only recently climbed the research agenda. The geopolitics of intended learning outcomes in the ESD debate, carries policy that produce dilemmas and challenges confronted with disciplinary traditions. In this article it is examined dialectically how the changing climate and the paradigm of sustainability have been dealt with in Danish geographical university education. It is shown how curriculum programs in higher geographical education have taken different approaches to address issues of sustainability and climate change and how geographers articulate their role and function as knowledge on human-environment interactions changes. The analysis of the geographical education reveal that geographers’ find their discipline contribute considerably to ESD, and thus the human environment theme seems to be associated more closely with sustainability issues.